Analysis of radial and halbach permanent magnet configurations for ceiling fan applications - Zulkarnain, N.F. (UK Simulation Society, 2017)
Permanent magnet motor offers various advantages such as simple construction and high efficiency which are highly demand in domestic appliances. The standard single-phase ceiling fan motors that are driven by the induction motor are inherently low efficiency. This paper presents an analysis on radial and Halbach permanent magnet array configurations of permanent magnet synchronous machine for ceiling fan. The proposed design of ceiling fan machine comprises a motor and a generator in one machine that implement a concept of the single rotor double stator. An analysis was conducted via finite element analysis to compare the performance of the flux distribution, air-gap flux density and back EMF between the conventional radial and Halbach permanent magnet machine. Overall, Halbach permanent magnet machine generates a high intensity of flux lines and flux density due to the self-magnetization features. However, the generated back EMF is not significant as compared to radial permanent magnet machines. Considering the simplicity of the design, radial array machine is identified as the optimized design configurations. © 2017, UK Simulation Society. All rights reserved.